(untitled) (International Journal of Environmental Sciences, 2025)
This study investigates the intersection of socio-demographic characteristics and environmental awareness within the marginalized Meo Muslim community of Nuh district, an area marked by socio-economic deprivation and ecological vulnerability. The primary objective was to assess how variables such as education, income, occupation, gender, and access to environmental information influence awareness levels in a context of historical marginalization. Employing a quantitative, cross-sectional design, data were collected from 150 participants selected through purposive and snowball sampling. A structured, culturally adapted questionnaire captured socio-demographic profiles and environmental awareness, with analysis involving descriptive statistics, Chi-square tests, and multiple regression modeling. Findings reveal a predominantly low level of environmental awareness, with 55.3% of participants scoring low, 36% moderate, and only 8.7% high. Education and access to information emerged as significant positive predictors (p < 0.05), while income and age showed no significant influence when other variables were controlled. Gender and age disparities were evident, with men and younger participants demonstrating comparatively higher awareness. The results underscore the critical role of formal education and information dissemination in fostering ecological consciousness in marginalized rural settings. The study concludes that targeted, culturally grounded awareness programs integrating traditional ecological knowledge with modern environmental education are essential to address both social inequities and environmental challenges in the Meo community.